Historical biogeography and local adaptation explain population genetic structure in a widespread terrestrial orchid. (21st March 2023) - Evans, Alexandra; de Kort, Hanne; Brys, Rein; Duffy, Karl J; Jersáková, Jana; Kull, Tiiu; Selosse, Marc-André; Tsiftsis, Spyros; Minasiewicz, Julita; Jacquemyn, Hans
Abstract: Background and Aims: Historical changes in environmental conditions and colonization–extinction dynamics have a direct impact on the genetic structure of plant populations. However, understanding how past environmental conditions influenced the evolution of species with high gene flow is challenging when signals for genetic isolation and adaptation are swamped by gene flow. We investigated the spatial distribution and genetic structure of the widespread terrestrial orchid Epipactis helleborine to identify glacial refugia, characterize postglacial population dynamics and assess its adaptive potential. Methods: Ecological niche modelling was used to locate possible glacial refugia and postglacial recolonization opportunities of E. helleborine . A large single-nucleotide polymorphism (SNP) dataset obtained through genotyping by sequencing was used to define population genetic diversity and structure and to identify sources of postglacial gene flow. Outlier analyses were used to elucidate how adaptation to the local environment contributed to population divergence. Key Results: The distribution of climatically suitable areas was restricted during the Last Glacial Maximum to the Mediterranean, south-western Europe and small areas in the Alps and Carpathians. Within-population genetic diversity was high in E. helleborine (mean expected heterozygosity, 0.373 ± 0.006; observed heterozygosity, 0.571 ± 0.012; allelic richness, 1.387 ± 0.007). Italy and central Europe are likely to have acted as important genetic sources during postglacial recolonization. Adaptive SNPs were associated with temperature, elevation and precipitation. Conclusions: Forests in the Mediterranean and Carpathians are likely to have acted as glacial refugia for Epipactis helleborine . Postglacial migration northwards and to higher elevations resulted in the dispersal and diversification of E. helleborine in central Europe and Italy, and to geographical isolation and divergent adaptation in Greek and Italian populations. Distinguishing adaptive from neutral genetic diversity allowed us to conclude that E. helleborine has a high adaptive potential to climate change and demonstrates that signals of adaptation and historical isolation can be identified even in species with high gene flow.